English Learning Model and Independence of Vocational School Students in the Pandemic Period - Kusmiyati; Ni Nyoman Sarmi (HM Publisher, 2022)
Learning independence is one of the important things in a learning process so that students have the responsibility to organize and discipline themselves, in addition to being able to develop learning abilities on their own accord. The problem that occurs at this time is the learning process that has been forced to be carried out at home through online learning, since the Covid 19 pandemic. The purpose of this research is to find out the online learning model of english in vocational high schools throughout the city of Surabaya during the pandemic and how high the influence of the level of independence is. students and the effect of learning models on learning outcomes of English learning at SMK Surabaya City during the pandemic. This research is quantitative research using a questionnaire for data collection. The population in this study were all English teachers in public and private vocational schools in the city of Surabaya as many as 278 people while the sample of this study was 74 people. The presentation of descriptive analysis in this study is the independent variable (X), the learning model variable (Y), and the learning outcome variable (Z). The results of the analysis in the study showed that the students' independence had an average of 2.93 which was included in the sufficient category. This means that the independence of SMK students throughout the city of Surabaya in learning English during the pandemic is quite good. The results of the descriptive analysis showed that the learning model applied during the pandemic in English subjects was good with an average score of 3.15. The coefficient of the learning model variable from the regression analysis is known to be 0.556. This shows that the learning model has a positive effect on learning outcomes. The better the learning model, the higher the learning outcomes produced. The significance value obtained is 0.000, which means that the learning model has a significant effect on learning English outcomes at SMK in Surabaya City during the pandemic.